A aposentadoria da pessoa com deficiência a luz do paradigma de inclusão proposto na Convenção da ONU em Nova Iorque - Borba, Juliana de Cássia Bento (2016)
In the present study, lectures about the disabled person in the Brazilian legal system, dealing initially the concept of person with disabilities and culminating with the theme treatment in the Brazilian legal system. It gives special emphasis to the Supplementary Law 142/2013, which deals with the pension benefit of the person's retirement with disabilities and recognizes the difference and regulates retirement with reduction of time for people with disabilities. The regulation of retirement, the LC 142, aimed to ensure differentiated criteria for retirement to the disabled, setting a historic achievement in recognition of the differences and the difficulties encountered daily by these citizens. The work is made from the corollary of the principle of equality and the new person protection paradigm with disabilities, chased from the New York Convention, favoring a new dealings in the search for effective social inclusion and enabling the establishment of a new model sustainable. Sustainability requires real social inclusion, from greater participation of persons with disabilities in society on an equal basis to other people. For this, the recognition and respect for differences is necessary in addition to the implementation of public policies and legislation for the protection and promotion of equality between different. Overcoming social segregation was the highest objective to be pursued and, despite legal advances, there is still much to be realized - and awareness - so that a significant portion of society can, in fact, fully exercise their rights. In Brazil, the Person with Disabilities Statute represented a great step in fostering social inclusion from mainly the effort as the overthrow of barriers, reducing differences and raising the priority of work. It is the work that we have the possibility of effective inclusion, ensuring equal opportunities to recognizably different